Optimization of aqueous Remazol Brilliant Blue R (RBBR) decolorization by trametes sp. pellets in Fluidized Bed Biological Reactor (FBBR) / Liza Ferina - Liza, Ferina (2013)
Decolorization of synthetic dye Remazol Brilliant Blue R (RBBR) by Trametes sp. pellets in fluidized bed biological reactor (FBBR) was studied. Initially, the decolorization process was performed using shaken flasks which contained 100 ml of RBBR aqueous solution and fungal pellets. The process was followed for 48 hours and the decolorization was analyzed at a visible spectrum of 590 nm. Response surface methodology (RSM) employing Box Behnken design at three factors i.e. initial concentration of RBBR, mass of pellet and pH was used to optimize decolorization process in shaken flasks. As the result, initial dye concentration was found to be a significant main factor to decolorization process compared to mass of pellets and pH. Meanwhile, maximum decolorization efficiency 67.9 ± 5.4% was achieved when 50 ppm initial concentration of dye, 4 gram of pellet and pH 5.6 were ran. Kinetic of RBBR decolorization in batch flask with optimum values of variables was also studied. The closest model to explain the kinetic of decolorization was the first order model with kinetic constant (k) = 0.071 h-1 and R2=0.964. Furthermore, the optimized variables in batch flask study to gather with various hydraulic retention time (HRT) and air flow rate were operated in continuous FBBR for 72 hours. From graphical analysis, the highest decolorization was recorded at 24 hr of HRT for all air flow rate tests. The effects of HRT and air flow rate in continuous reactor were analyzed by second order polynomial model. For the main and interaction factor, both of HRT and air flow rate were found to be significant on RBBR decolorization. The maximum decolorization was obtained at 24 hr of HRT and 0.6 l/min of air flow rate. Kinetic study in FBBR was studied by comparing plug flow and mixed flow model. Based on kinetic constants from batch study (0.071 hr-1) and both of models, the exit concentration of aqueous RBBR could be predicted. The plug flow model was chosen as the fit model to illustrate the observation process in FBBR, especially for 0.6 l/min of air flow rate. Keywords: decolorization, Trametes sp, response surface methodology, kinetic study, fluidized bed biological reactor.